A MONETARY BUSINESS CYCLE MODEL FOR INDIA. (19th November 2019) - Banerjee, Shesadri; Basu, Parantap; Ghate, Chetan
Abstract : A New Keynesian monetary business cycle model is constructed to study why monetary transmission in India is weak. Our models feature banking and financial sector frictions as well as an informal sector. The predominant channel of monetary transmission is a credit channel. Our main finding is that base money shocks have a larger and more persistent effect on output than an interest rate shock, as in the data. The presence of an informal sector hinders monetary transmission. Contrary to the consensus view, financial repression in the form of a statutory liquidity ratio and administered interest rates, does not weaken monetary transmission. ( JEL E31, E32, E44, E52, E63)